2011
DOI: 10.1186/1297-9686-43-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of European grayling (Thymallus thymallus) populations in Serbia, based on mitochondrial and nuclear DNA analyses

Abstract: BackgroundThe structure and diversity of grayling (Thymallus thymallus) populations have been well studied in most of its native habitat; however the southernmost populations of the Balkan Peninsula remain largely unexplored. The purpose of this study was to assess the genetic diversity of Serbian grayling populations, detect the impact of stocking and provide guidelines for conservation and management.MethodsEighty grayling individuals were collected from four rivers (Ibar, Lim, Drina and Rzav). The mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
(66 reference statements)
3
19
0
Order By: Relevance
“…The other four haplotypes (i.e. Da23, Da25, Da27 and Da29) had been previously identified in the Danube drainage of Slovenia and Serbia (Weiss et al, 2002;Marić et al, 2011). In this study, the haplotypes Da23, Da25 and Ad7 were found to predominantly occur in Slovenia (frequency of 80-100%), while the others (i.e.…”
Section: Mitochondrial Dna Sequence Analysissupporting
confidence: 64%
See 3 more Smart Citations
“…The other four haplotypes (i.e. Da23, Da25, Da27 and Da29) had been previously identified in the Danube drainage of Slovenia and Serbia (Weiss et al, 2002;Marić et al, 2011). In this study, the haplotypes Da23, Da25 and Ad7 were found to predominantly occur in Slovenia (frequency of 80-100%), while the others (i.e.…”
Section: Mitochondrial Dna Sequence Analysissupporting
confidence: 64%
“…Additional grayling haplotypes from GenBank (accession numbers AF522395-AF522452; HM636922-HM636924) were used in analysis. To assign individual haplotypes and clades to the previously identified within the European grayling, data from this study were aligned against haplotypes from each clade (Weiss et al, 2002;Marić et al, 2011) and compared with them. T. arcticus (AF522453), T. grubei (AF522454) and T. brevirostris (AF522455) were used as outgroup taxa.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…trutta of two indigenous lineages sensu Bernatchez (2001): Danubian (Da) and Adriatic (Ad) in three drainages: Black Sea, Aegean Sea (Southern Serbia) and Adriatic Sea (South-western Serbia), as well as the Atlantic (At) brown trout introduced into the Da and Ad stocks. Serbia also homes a limited stock of European grayling Thymallus thymallus that belongs to the distinct Balkan lineage in the southernmost part of its dispersal area with only one isolated stock hitherto introduced there so far (Marić et al, 2011). In addition to the widespread brown trout mtDNA strains in both indigenous lineages, there are few narrowly distributed (Marić et al, 2006;Tošić et al, 2014).…”
Section: Introductionmentioning
confidence: 99%